Pitfalls in Calculating Cash Flow from Operations. - Drtina, Ralph H.; Largay III, James A. (The Accounting Review, 1985)
ABSTRACT: Although many firms now prepare a cash-based statement of changes in financial position, reported "funds from operations" is typically a measurement of working capital. The statement reader wishing to determine cash flow from operations must use a series of indirect adjustments to do so. Our purpose in this paper is to identify the inherent difficulties the reader encounters when using this indirect method to convert reported funds from operations to a cash flow amount. We demonstrate how the indirect method will in fact not equal actual cash flow from operations because of numerous conceptual and practical problems encountered when applying the necessary adjustments. We develop illustrations of these problems, and we show how cash flow from operations calculated by the indirect method is, at best, an estimate of actual cash provided by operations.